Atypical myocardial infarction masquerading as gastroenteritis - Mahmood, Shafqat; Rashid, Rahim Abdul; Ali, Mohammad (International Journal of Research in Medical Sciences, 2023)
Acute coronary syndrome (ACS) encompasses unstable angina and myocardial infarction (MI). MI typically presents as chest pain that may radiate to the arm or jaw and is described as dull, heavy, tight, or crushing. However, it may present atypically with symptoms other than chest pain including epigastric pain, often described as burning in character or like indigestion. This is a case of a 51-year-old patient who presented with symptoms of epigastric pain, nausea and vomiting resembling gastroesophageal disease. The patient was initially evaluated by a physician as a non-urgent case of gastroenteritis. Following further assessment due to ongoing symptoms, he was diagnosed with ST elevation MI (STEMI) and treated according to ACS treatment guidelines. To accurately diagnose ACS, clinicians must demonstrate competent communication, history taking and physical examination skills, identify red flags and make use of appropriate investigations. Correct medications and timely referral to secondary care services is vital to prevent morbidity and mortality.